A Synthetic Toolbox for the In Situ Formation of Functionalized Homo‐ and Heteropolysaccharide‐Based Hydrogel Libraries. Issue 52 (16th November 2016) - Dibbert, Nick; Krause, Andreas; Rios‐Camacho, Julio‐Cesar; Gruh, Ina; Kirschning, Andreas; Dräger, Gerald
Abstract: A synthetic toolbox for the introduction of aldehydo and hydrazido groups into the polysaccharides hyaluronic acid, alginate, dextran, pullulan, glycogen, and carboxymethyl cellulose and their use for hydrogel formation is reported. Upon mixing differently functionalized polysaccharides derived from the same natural precursor, hydrazone cross‐linking takes place, which results in formation of a hydrogel composed of one type of polysaccharide backbone. Likewise, hydrogels based on two different polysaccharide strands can be formed after mixing the corresponding aldehydo‐ and hydrazido‐modified polysaccharides. A second line of these studies paves the way to introduce a biomedically relevant ligand, namely, the adhesion factor cyclic RGD pentapeptide, by using an orthogonal click reaction. This set of modified polysaccharides served to create a library of hydrogels that differ in the combination of polysaccharide strands and the degree of cross‐linking. The different hydrogels were evaluated with respect to their rheological properties, their ability to absorb water, and their cytotoxicity towards human fibroblast cell cultures. None of the hydrogels studied were cytotoxic, and, hence, they are in principal biocompatible for applications in tissue engineering. Abstract : Gels by double click : A toolbox concept based on differently functionalized polysaccharides (see figure) provides access to new hydrogels, which in some cases were conjugated with the adhesion factor c RGDfK pentapeptide. Hydrogels tested did not exert cytotoxic activity and displayed the same biocompatibility as collagen/Matrigel®, a scaffold material routinely applied for cardiac tissue engineering.